KEDUDUKAN PERSEROAN TERBATAS PAN UNITED DALAM PERKARA KEPAILITAN YANG DILAKUKAN OLEH KOMISARIS PERSEROAN TERBATAS PAN UNITED ( STUDI PERKARA KEPAILITAN NOMOR 14/ PAILIT/ 2011/ PN. NIAGA MEDAN) - Hutagaol, Ririn Erida; Hanifah, Mardalena; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Bankruptcy in Indonesia is regulated in Law Number 37 Year 2004 on Bankruptcy and Suspension of Payment. Limited liability company has an organ that has the authority and responsibility of its own which is stipulated in the Articles of Association and Law Number 40 Year 2007 on Limited Liability Companies. This never happened in the Limited Liability Pan United that bankrupted by Chee Kong Chui, through the decision of the Commercial Court of Medan in Case No. 14 / Pailit / 2011 / PN. Medan Niaga, the verdict PT. Pan United appealed to the Supreme Court of the Republic of Indonesia, the Supreme Court accepted the appeal application PT. Pan United and Commercial Court canceled the verdict of the Supreme Court of Medan via Decision No. 188 / KPdt.Sus / 2012.As for the purpose of this thesis are: First, What is the status Limited Liability Company in the bankruptcy case number 14 / Pailit / 2011 / PN. Medan Niaga; second, How considerations bankruptcy judge in case number 14 / Pailit / 2011 / PN. Medan Niaga is already with the provisions of applicable law. This type of research can be classified on the kind of normative juridical research, because this research can be classified in this type of research on library materials. Source of data used is primary data, secondary data and data tertiary data collection techniques in this research study of literature. Analysis of the data used in this study is qualitative.The results showed that: First, the position of Limited Liability Pan United is not the debtor of the applicant Kong Chee Chui clearly that the Commissioner Song Ghee Hong outside kewenagannya acts as commissioner and PT. Pan United did not exist receive the loan money. This is made clear in Article 45 Code of Commerce and Article 1656 of the Civil Code. Second, the considerations of judges at the Commercial Court of Medan has misapplied the law by deciding PT. Pan United's bankruptcy with all the legal consequences. See the position of PT. Pan United that is not a debtor of Chee Kong Chui. Considerations Judges of the Supreme Court in ruling No. 188 / KPdt.Sus / 2012 which has the right to annul the decision of the Commercial Court of Medan.Advice, Before doing borrowing money agreement, creditors must make Deed agreement between the creditor and the debtor prior to clearly understand the purpose and intention of borrowing money by knowing the position of the Borrower. The commercial court as the court who coined the authority to hear the case of bankruptcy should be right in deciding a case of bankruptcy in order to provide legal certainty to both parties in resolving casesKeywords: Position- Limited company-Commissioner Bankruptcy